PERCERAIAN ORANG TUA DAN IMPLIKASINYA TERHADAP PENDIDIKAN ANAK DALAM ISLAM - Rima Hadayati (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2016)
Every child is born in a state of nature, then both his parents who make it Jewish, or Zoroastrian Nashrani (HR.Muslim). Implied meaning of the hadith is that the formation of the child's personality is influenced by upbringing and education of parents. Basically every child wants to live with his parents, didikik, nurtured and given affection filled by both parents. However, if the household of his parents could not be maintained in this case happens disharmony or other factors so that his parents divorced, the children are victims of divorce of their parents. Divorce for children is